A solid polymer electrolyte membrane, preparation method and lithium metal battery
By using PVDF-HFP, LiFSI and THF to prepare solid polymer electrolyte membranes, the problems of low conductivity and poor mechanical strength of organic polymer solid electrolytes in the prior art under low temperature conditions are solved, and the stability and cycle life of lithium metal batteries are significantly improved.
Patent Information
- Application Number
- CN202411774355.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing organic polymer solid electrolytes have low ionic conductivity and poor mechanical strength under low temperature conditions. The residual organic solvents in the preparation process cause side reactions with lithium metal, reducing battery stability.
Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is used as the supporting framework of the electrolyte membrane, lithium bisfluorosulfonimide (LiFSI) is used as the electrolyte component, and tetrahydrofuran (THF) is used as the solvent. PVDF-HFP is uniformly dissolved in THF by sealing heating, and then added LiFSI is added to dry to form a solid polymer electrolyte membrane.
The mechanical strength and ionic conductivity of the electrolyte are significantly improved, the side reaction between residual solvents and lithium metal is eliminated, the stability and cycle life of lithium metal batteries are improved, and the high capacity retention rate is achieved.
Smart Images

Figure CN119253056B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a solid polymer electrolyte membrane, a preparation method and a lithium metal battery. Background Art
[0002] Lithium metal batteries use lithium metal as the negative electrode and have higher energy density and longer life than the widely used lithium-ion batteries. Replacing traditional liquid electrolytes with solid electrolytes can inhibit the growth of lithium dendrites during the cycle of lithium metal batteries and improve the safety of lithium batteries. Solid electrolytes are mainly divided into two categories: inorganic solid electrolytes and polymer solid electrolytes. Although inorganic solid electrolytes have high ionic conductivity, good thermal stability and strong mechanical strength, they also face a series of challenges such as poor interface stability, poor low-temperature performance, high brittleness and processing difficulties, which limit their practical applications. Organic polymer solid electrolytes have better processability, flexibility, interface stability, low-temperature performance and lower cost, and are easier to achieve large-scale production in practical applications.
[0003] However, the existing organic polymer solid electrolyte technology has at least the following technical problems:
[0004] Commonly used organic polymer solid electrolytes such as polyethylene oxide (PEO) have poor mechanical strength, and the electrolyte ion conductivity is low under low temperature conditions.
[0005] Organic solvents commonly used in the preparation of organic polymer solid electrolytes, such as N , N -Dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP) and dimethyl sulfoxide (DMSO) are thermodynamically unstable with lithium metal. Residual solvents in solid polymer electrolytes will produce side reactions with lithium metal and corrode lithium metal, thus seriously reducing the stability of the battery. Summary of the invention
[0006] To solve the above problems, the present invention provides a solid polymer electrolyte membrane, a preparation method and a lithium metal battery, which eliminates the side reaction of residual solvents in the organic polymer solid electrolyte in the prior art, improves the mechanical strength and ion conductivity. This improved electrolyte achieves a stable lithium stripping / deposition cycle of more than 9,000 hours in a lithium symmetric battery. The interface stability of the electrolyte and the lithium metal negative electrode and the capacity retention rate of the whole battery are significantly improved.
[0007] The technical solution adopted by the present invention is as follows:
[0008] A solid polymer electrolyte membrane, comprising a polymer polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), lithium bis(fluorosulfonyl)imide (LiFSI) and an organic solvent tetrahydrofuran (THF); the polyvinylidene fluoride-hexafluoropropylene is a supporting skeleton of the electrolyte membrane, the residual tetrahydrofuran solvent is adsorbed in a pore network formed by the polyvinylidene fluoride-hexafluoropropylene, the lithium bis(fluorosulfonyl)imide is dissolved in the tetrahydrofuran to ionize lithium ions, and the residual tetrahydrofuran solvent interacts with the lithium ions to form [Li(solvent) x ] + Solvation structure. Meanwhile, the tetrahydrofuran in the present invention does not react with lithium metal and can form a stable negative electrode interface with lithium metal, which is specifically manifested in that the cycle time of the lithium symmetric battery is as long as 9000 hours.
[0009] A method for preparing a solid polymer electrolyte membrane comprises the following steps:
[0010] (1) adding tetrahydrofuran, an organic solvent, to polyvinylidene fluoride-hexafluoropropylene, sealing and heating, so that the polyvinylidene fluoride-hexafluoropropylene is uniformly dissolved in tetrahydrofuran;
[0011] (2) adding lithium bis(fluorosulfonyl)imide salt to the mixed solution obtained in step (1) and stirring evenly;
[0012] (3) The mixed solution obtained in step (2) is heated and dried to obtain a solid polymer electrolyte membrane.
[0013] Furthermore, the mass ratio of the bis(fluorosulfonyl)imide lithium salt, poly(vinylidene fluoride-hexafluoropropylene) and tetrahydrofuran is 3:4:121.
[0014] Furthermore, in step (1), the sealing heating temperature is 60°C-70°C.
[0015] Furthermore, in step (3), the heating and drying temperature is 30°C-35°C, and the time is 2-2.5 hours.
[0016] A lithium metal battery, wherein the active material of the positive electrode of the battery cell of the lithium metal battery is one or more of lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel manganese oxide, and nickel cobalt manganese ternary positive electrode; the negative electrode material is lithium metal; the electrolyte is the above-mentioned solid polymer electrolyte membrane or the solid polymer electrolyte membrane prepared by the above-mentioned method. According to actual needs, corresponding button, soft pack and other types of lithium metal batteries can be prepared.
[0017] The beneficial effects of the present invention are:
[0018] The solid polymer electrolyte membrane prepared by the preparation method provided by the present invention has a dense and continuous microstructure, good mechanical properties, namely a high Young's modulus (46.47MPa); and good ionic conductivity (at 20°C). ; at -20℃ ).
[0019] The solid polymer electrolyte membrane provided by the present invention exhibits super stability with the lithium metal negative electrode, which is specifically manifested in that the symmetrical battery has an ultra-long cycle life (at 30°C, 0.1 mA cm -2 , 0.1mAh cm -2 conditions, up to 9000 hours).
[0020] The lithium metal full battery using the solid polymer electrolyte membrane provided by the present invention has a higher capacity retention rate (500 cycles at 30° C., the capacity retention rate is 76.7%).
[0021] The preparation method of the present invention has simple process, does not require additives, can be prepared using a single solvent, a single polymer, and a single lithium salt, and has low cost.
[0022] The solid polymer electrolyte membrane of the present invention has good mechanical properties and good compatibility with lithium metal negative electrodes, and also has good ionic conductivity at room temperature or even low temperature conditions. After being applied to lithium metal batteries, it can improve the stability of lithium metal negative electrodes and thus significantly improve the battery capacity retention rate and cycle life of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is an electron microscope photograph of the solid polymer electrolyte membrane provided in Example 1 of the present invention.
[0024] Figure 2 It is an electron microscope photograph of the solid polymer electrolyte membrane provided in Comparative Example 1 of the present invention.
[0025] Figure 3 It is a stress-strain comparison diagram of the solid polymer electrolyte membrane provided by Example 1 of the present invention and the solid polymer electrolyte membrane provided by Comparative Example 1 under uniaxial tension.
[0026] Figure 4 The thickness is 100 provided in Example 1 of the present invention. The electrochemical impedance spectra of the solid polymer electrolyte membrane at different temperatures, from which the ionic conductivity of Example 1 at 20°C can be calculated to be .
[0027] Figure 5 The thickness is 100 provided in Comparative Example 1 of the present invention. Electrochemical impedance spectra of solid polymer electrolyte membrane at different temperatures, from which the ionic conductivity of comparative example 1 at 20°C can be calculated to be .
[0028] Figure 6 This is a comparison chart of the cycle performance of the lithium symmetric battery provided in Example 2 of the present invention and the lithium metal symmetric battery provided in Comparative Example 2.
[0029] Figure 7 This is a comparison chart of the cycle performance of the lithium metal full battery provided in Example 3 of the present invention and the lithium metal full battery provided in Comparative Example 3.
[0030] Figure 8 This is a flow chart of the method for preparing a solid polymer electrolyte provided in Example 1 of the present invention.
[0031] Fig. 9 This is a graph showing the result after lithium metal is immersed in the organic solvent used for the solid polymer electrolyte membrane provided in Example 1 of the present invention for 1000 hours. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further explained in detail below with reference to the accompanying drawings and specific examples.
[0033] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art. Example 1
[0034] like Figure 8 As shown, a solid polymer electrolyte membrane, the specific preparation steps are as follows:
[0035] (1) 0.44 g of polyvinylidene fluoride-hexafluoropropylene was added to a reaction bottle, and 13.31 g of an organic solvent, tetrahydrofuran, was added thereto. The reaction bottle was sealed and heated at 65°C to uniformly dissolve the polyvinylidene fluoride-hexafluoropropylene in tetrahydrofuran.
[0036] (2) Add 0.33 g of lithium bis(fluorosulfonyl)imide salt to the mixed solution obtained in step (1) and stir evenly;
[0037] (3) Pour the mixed solution obtained in step (2) into a glass dish, cover the top of the glass dish with a layer of non-woven fabric, put it into an oven, and dry it at 30° C. for 2 hours to obtain a solid polymer electrolyte membrane. Example 2
[0038] A lithium symmetrical battery, the specific preparation steps of which are as follows:
[0039] The battery negative electrode shell, gasket, current collector, lithium metal, the solid polymer electrolyte membrane prepared in Example 1, lithium metal, current collector, and battery positive electrode shell are stacked together in order. The battery as a whole is placed in a hydraulic press and pressed to obtain a button battery. Example 3
[0040] A lithium metal battery, the specific preparation steps of which are as follows:
[0041] The battery negative electrode shell, gasket, current collector, lithium metal, solid polymer electrolyte membrane prepared in Example 1, lithium iron phosphate positive electrode, current collector, and battery positive electrode shell are stacked together in order. The battery as a whole is placed in a hydraulic press and pressed to obtain a button battery. Comparative Example 1
[0042] A solid polymer electrolyte membrane, the specific preparation steps of which are as follows:
[0043] (1) Add 0.44 g of polyvinylidene fluoride-hexafluoropropylene into the reaction bottle and add 12.8 g of organic solvent. N , N - dimethylformamide, sealed, heated at 60°C to make polyvinylidene fluoride-hexafluoropropylene uniformly dissolved in N , N - dimethylformamide;
[0044] (2) Add 0.33 g of lithium bis(fluorosulfonyl)imide salt to the mixed solution obtained in step (1) and stir evenly;
[0045] (3) Pour the mixed solution obtained in step (2) into a glass dish, cover the top of the glass dish with a layer of non-woven fabric, put it into an oven, and dry it at 65° C. for 20 hours to obtain a solid polymer electrolyte membrane. Comparative Example 2
[0046] A lithium symmetrical battery, the specific preparation steps of which are as follows:
[0047] The battery negative electrode shell, gasket, current collector, lithium metal, solid polymer electrolyte membrane prepared in Comparative Example 1, lithium metal, current collector, and battery positive electrode shell are stacked together in order. The battery as a whole is placed in a hydraulic press and pressed to obtain a lithium symmetrical battery. Comparative Example 3
[0048] A lithium metal full battery, the specific preparation steps of which are as follows:
[0049] The battery negative electrode shell, gasket, current collector, lithium metal, solid polymer electrolyte membrane prepared in Comparative Example 1, lithium iron phosphate positive electrode, current collector, and battery positive electrode shell are stacked together in order. The battery as a whole is placed in a hydraulic press and pressed to obtain a full lithium metal battery.
[0050] Figure 3 The stress-strain comparison diagram of the solid polymer electrolyte membrane provided in Example 1 and the solid polymer electrolyte membrane provided in Comparative Example 1 under uniaxial tension shows that the Young's modulus of the solid electrolyte membrane obtained in Example 1 reaches 46.47 MPa, while the Young's modulus of the solid electrolyte membrane obtained in Comparative Example 1 is only 8.46 MPa. In terms of ionic conductivity, the solid electrolyte membrane obtained in Example 1 is 2.61×10 -3 , at -20℃, it is 8.16×10 -4 ( Figure 4 ); while the solid electrolyte membrane obtained in Comparative Example 1 has a thickness of 2.81×10 -4 , at -20℃, only 2.14×10 -4 ( Figure 5 ).
[0051] Under the test environment of 30°C, the battery life of the lithium symmetrical battery provided in Example 2 reaches 9000 hours, while the battery life of the lithium symmetrical battery provided in Comparative Example 2 is only 400 hours ( Figure 6 At the same time, the capacity retention rate of the lithium metal full battery provided in Example 3 was 76.7% after 500 cycles; while the capacity retention rate of the lithium metal full battery provided in Comparative Example 3 was only 21.5% after 500 cycles ( Figure 7 ).
[0052] The solid polymer electrolyte membrane provided in the embodiment of the present application includes a polymer polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), lithium bis(fluorosulfonyl)imide (LiFSI) and an organic solvent tetrahydrofuran (THF).
[0053] Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) plays a role of skeleton support in the solid polymer electrolyte membrane. The residual tetrahydrofuran solvent is adsorbed in the pore network composed of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and the tetrahydrofuran interacts with the lithium salt to form [Li(solvent) x ] +Solvation structure significantly improves ionic conductivity. The attraction between THF dipole and PVDF-HFP dipole is smaller than that between PVDF-HFP dipole and PVDF-HFP dipole. Therefore, during the evaporation process, the THF dipole will not aggregate the PVDF-HFP molecular chains into a cluster. On the contrary, the PVDF-HFP molecular chains can be evenly laid out to form a dense honeycomb polymer structure. Figure 1 As shown, it is an electron microscope photo of the solid polymer electrolyte membrane provided in Example 1, showing its dense microstructure, so that the Young's modulus of the solid polymer electrolyte membrane provided in Example 1 reaches 46.47MPa ( Figure 3 ). In contrast, Figure 2 As shown, the electron microscope photograph of the solid polymer electrolyte membrane provided in Comparative Example 1 shows its spherical discontinuous structure, thereby showing a lower Young's modulus (8.46 MPa, Figure 3 ).
[0054] The [Li(solvent) x ] + The solvated structure contributes to the high ionic conductivity of the electrolyte. At the same time, tetrahydrofuran (THF) has a low freezing point and has no side reaction with lithium metal, so that the solid polymer electrolyte membrane can still maintain high ionic conductivity at room temperature or even low temperature. The ionic conductivity of the solid polymer electrolyte membrane provided in Example 1 is 2.61×10 -3 ; at -20℃, 8.16×10 -4 ( Figure 4 ). Since the organic solvent tetrahydrofuran (THF) used in the preparation of the solid polymer electrolyte membrane is more stable to the negative electrode lithium metal and has fewer side reactions. After the lithium metal is immersed in tetrahydrofuran (THF) for 1000 hours, the tetrahydrofuran (THF) remains clear and the lithium metal remains shiny ( Fig. 9 ). This stability enables the full battery or symmetrical battery using the solid polymer electrolyte membrane provided in Example 1 to have a higher battery capacity retention rate and an ultra-long cycle life. Under the test condition of 30°C, the life of the lithium symmetrical battery provided in Example 2 can reach 9000 hours ( Figure 6 ), the capacity retention rate of the lithium metal full battery provided in Example 3 after 500 cycles is 76.7% ( Figure 7 ).
[0055] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a solid polymer electrolyte membrane, characterized in that: The following steps are involved: (1) adding tetrahydrofuran, an organic solvent, to polyvinylidene fluoride-hexafluoropropylene, sealing and heating, so that the polyvinylidene fluoride-hexafluoropropylene is uniformly dissolved in tetrahydrofuran; (2) adding lithium bis(fluorosulfonyl)imide salt to the mixed solution obtained in step (1) and stirring evenly; (3) heating and drying the mixed solution obtained in step (2) to obtain a solid polymer electrolyte membrane, wherein the heating and drying temperature is 30° C.-35° C. and the time is 2-2.5 hours; The solid polymer electrolyte membrane comprises a polymer polyvinylidene fluoride-hexafluoropropylene, a bis(fluorosulfonyl)imide lithium salt and an organic solvent tetrahydrofuran; the polyvinylidene fluoride-hexafluoropropylene is a supporting skeleton of the electrolyte membrane, the residual tetrahydrofuran solvent is adsorbed in a pore network formed by the polyvinylidene fluoride-hexafluoropropylene, the bis(fluorosulfonyl)imide lithium salt is dissolved in tetrahydrofuran to ionize lithium ions, and the tetrahydrofuran and the lithium ions interact to form [Li(solvent) x ] + Solvation structure.
2. The method for preparing a solid polymer electrolyte membrane according to claim 1, characterized in that: The mass ratio of the bis(fluorosulfonyl)imide lithium salt, poly(vinylidene fluoride-hexafluoropropylene) and tetrahydrofuran is 3:4:
121.
3. The method for preparing a solid polymer electrolyte membrane according to claim 1, characterized in that: In step (1), the sealing heating temperature is 60°C-70°C.
4. A lithium metal battery, characterized in that: The active material of the positive electrode plate of the lithium metal battery cell is one or more of lithium iron phosphate, lithium nickel oxide, lithium cobalt oxide, lithium iron manganese phosphate, lithium manganese oxide, lithium nickel manganese oxide, and nickel cobalt manganese ternary positive electrode; the negative electrode material is lithium metal; and the electrolyte is a solid polymer electrolyte membrane prepared by the method described in any one of claims 1 to 3.
Citation Information
Patent Citations
Composite electrolyte membrane for all-solid-state lithium metal battery as well as preparation method and application of composite electrolyte membrane
CN118281309A